Crafting of Photothermal Cobalt/Sulfur Doped Manganese Selenide for Extreme‐Temperature‐Tolerant Flexible Zinc‐Air Batteries - Wang, Wenjing; Wang, Jiajian; Pan, Shuang; Wang, Zheng‐Jun; Wang, Shun; Chen, Yihuang; Chen, Luya (Advanced functional materials, 2025)
Zinc–air batteries (ZABs) offer exciting potential for energy storage in emerging flexible electronics. However, despite the rapid progress achieved, the persistent sluggishness in oxygen electrocatalysis remains a significant barrier hindering the widespread utilization of ZABs, especially under demanding conditions. In this research work, cost‐effective manganese selenide (MnSe) is integrated as an intermetallic catalyst and its overall catalytic performance is subsequently enhanced by introducing cobalt and sulfur doping, in conjunction with nitrogen‐doped graphene, resulting in excellent performance catalysts with significant photothermal response and extreme temperature adaptability. The resulting Co,S‐MnSe/N‐rGO catalyst, when locally heated with photothermal assistance, accelerates reaction kinetics and promotes active site and surface reconstruction, as validated by operando Raman analysis and modeling. The activity index ∆ E is notably reduced to 0.584 V, surpassing most electrocatalysts (usually >0.700 V). Encouragingly, the photothermal electrocatalyst showcases remarkable merits of supreme power density (301 mW cm −2 , equivalent to 3 times that of conventional Pt/Ru‐based ZAB), and ultralong lifespan (5500 cycles) for liquid ZABs, and exceptional performance with extreme‐condition tolerance (broad temperature range from –40 to 60 °C and significant deformation) for flexible ZABs, offering a promising avenue for next‐generation high‐performance electronic reserve devices.